2016
DOI: 10.1177/2048872615610886
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in outcomes in patients with acute coronary syndrome in the current era: A review

Abstract: Coronary heart disease is the most common cause of death worldwide. In the United Kingdom in 2010, over 80,000 deaths were attributed to coronary heart disease, and one in 10 female deaths were due to coronary heart disease. Acute coronary syndrome, a subset of coronary heart disease, was responsible for 175,000 inpatient admissions in the United Kingdom in 2012. While men have traditionally been considered to be at higher risk of acute coronary syndrome, various studies have demonstrated that women often suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 85 publications
(147 reference statements)
4
27
0
Order By: Relevance
“…In fully adjusted models, women in our study were less likely than men to receive LLDs, ACEIs and ICPs, and of these interventions least likely to receive ICPs. Several other studies from the general population have also demonstrated that women are less likely to receive diagnostic and therapeutic invasive CVD‐interventions than men , and that women have higher mortality after invasive procedures . Women are less likely to have ST‐elevation myocardial infarction and more likely to have either none or atypical symptoms at the time of MI , possibly partly explained by female‐specific characteristics in macro‐and microvasculature .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In fully adjusted models, women in our study were less likely than men to receive LLDs, ACEIs and ICPs, and of these interventions least likely to receive ICPs. Several other studies from the general population have also demonstrated that women are less likely to receive diagnostic and therapeutic invasive CVD‐interventions than men , and that women have higher mortality after invasive procedures . Women are less likely to have ST‐elevation myocardial infarction and more likely to have either none or atypical symptoms at the time of MI , possibly partly explained by female‐specific characteristics in macro‐and microvasculature .…”
Section: Discussionmentioning
confidence: 96%
“…The reasons for these poorer outcomes remain unclear, but it is likely that multiple factors play a role, both before and after an event. Importantly, there is increasing evidence of delayed or less intensive use of medical and invasive procedures for diagnostic evaluation and treatment of MI and stroke among women compared to men . A previous study in the general population also demonstrated an inverse association between in‐hospital mortality after MI and the number of CVD risk factors that were present in an individual .…”
Section: Introductionmentioning
confidence: 99%
“…1 Additionally, women have more co-morbidities at the time of their ACS event, including a higher prevalence of diabetes, hypertension, heart failure, atrial fibrillation, chronic kidney disease, peripheral arterial disease, and depression. 1,23. Women are also more likely to have a non-ST-elevation MI (NSTEMI) and non-obstructive coronary artery disease when they present with ACS. 24 These differences may influence the timeliness of symptom recognition and interpretation and their decision whether to seek care.…”
Section: Introductionmentioning
confidence: 99%
“…18 Of note, a recent investigation observed that female AMI patients were less likely to receive optimal medical therapy and care during the hospitalization of the acute event than their male counterparts. 19 Similarly, the results of a pooled analysis of patients undergoing coronary intervention revealed that women had a significantly higher 1-year morality rate compared to men that could not be explained by baseline characteristics, infarction size and postinfarction cardiac functioning-rather triggered by poor post-AMI patient care. 20 Those results foster the clinical importance of the observed gender gap, concluding that women may have better outcomes if treated with the same level of both invasive management and post-AMI care as their male counterparts.…”
Section: Differences In Elderly Patients With Myocardial Infarction Imentioning
confidence: 99%
“…Women presenting with acute myocardial infarction (AMI) are still managed in a much less aggressive and invasive way than men. 18,19 However, women who received any reperfusion strategy were found to have an even lower risk of death compared to male individuals. 18 Of note, a recent investigation observed that female AMI patients were less likely to receive optimal medical therapy and care during the hospitalization of the acute event than their male counterparts.…”
mentioning
confidence: 99%